OC-034 Probiotics for the prevention of antibiotic associated diarrhoea in the older inpatient population; a systematic review and meta-analysis. (22nd June 2015) - Parisinos, CA; Ooi, JL; Lindsay, JO; Parkes, GC
Abstract : Introduction: Probiotics are live microorganisms intended to confer a health benefit when consumed, 1 and have been advocated for the prevention of antibiotic associated diarrhoea (AAD). Older patients are more susceptible to AAD compared to the general adult population. We conducted a systematic review and meta-analysis of the literature on probiotic use for the prevention of AAD in this patient group. Method: Two independent reviewers identified and critically appraised randomised controlled trials (RCTs) of probiotics from electronic databases PubMed and EMBASE (from date of inception to Jan 2015) for the prevention and treatment of AAD in hospital patients with mean age >60 years. Results: Eleven RCTs met inclusion criteria. The pooled relative risk (RR) in a DerSimonian-Laird random-effects meta-analysis of 11 RCTs, which included 4292 participants, showed a reduction in AAD (RR 0.67, 95% confidence interval (CI), 0.48 to 0.95; p = 0.02; I 2 = 64%). Subgroup genus analysis demonstrated a significant risk reduction with only Lactobacillus based probiotics (RR 0.51, CI 0.39 to 0.67, p < 0.00001, I 2 = 0%). Only 3/11 demonstrated adequate power. Adverse events were reported in only 6/11 RCTs, with no serious events attributed to probiotic use. Conclusion: Pooled results demonstrate that probiotics are associated with a risk reduction in AAD in older inpatients. Subgroup analysis demonstrated that this benefit is derived from Lactobacillus-only probiotics, an attractive candidate for future research. Disclosure of interest: None Declared. Reference: FAO, WHO. Health and nutritional properties of probiotics in food including powder milk with live lactic acid bacteria. 2001. ftp://ftp.fao.org/ed/esn/food/probio_report_en.pdf